Research on the influence mechanism of digital economy on the development of the sports and health industry in China - Haonan Sun; Maoteng Cheng; Fugao Jiang (Scientific Reports)
Abstract Digital technology’s quick adoption has given sectors a fresh boost to overcome long-standing growth barriers. The sports and health sector are now dealing with systemic issues such uneven regional development, poor service delivery, and resource misallocation. Accurately determining the digital economy’s driving force in the sports and health sector has emerged as a crucial issue for modernizing health governance and encouraging the creation of new, high-caliber productive forces. By building an evaluation index system for their development, this study determines the development indices of the digital economy and the sports and health industries using panel data from 270 Chinese cities at the prefecture level between 2011 and 2023. Additionally, the bidirectional fixed effect model and the mediation model are used to experimentally assess the direct promoting effect of the digital economy on the growth of the sports and health business, and a systematic analysis of its multi-level transmission mechanism is conducted. The findings of the study show that: (1) The growth of the sports and health sector can be greatly aided by the digital economy, and this conclusion has passed a number of robustness tests. (2) Mechanism analysis shows that through cost-saving effects, the digital economy can indirectly support the growth of the sports and health sector. (3) According to regional heterogeneity analysis, the spatial spillover impact is evident in the western region, which has failed the significance test, whereas the effect is more substantial in the eastern and central regions. The findings of this study demonstrate the important contribution of the digital economy to the growth of the sports and health sector, offering businesses and governments helpful resources.